AKTIVITAS SISWA SMKN 1 SERANG TERHADAP PENGGUNAAN JAM KOSONG DI KELAS - Huswatun Hasanah; Zhogi Achmad Panusuan; Firdaus Firdaus (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2023)
This is Education is a science that studies how to improve human quality in order to develop in a global world. Education in this country is not without problems. Not a few problems in the world of education are in the spotlight. One of the interesting things to highlight is the problem of free hours in class when learning is taking place at school. The existence of empty class hours at school can affect student delinquency. Research on student activities during free hours was conducted on 39 class XI students at SMKN 1 Kota Serang using a survey research method. The data collection technique used was a research instrument in the form of a questionnaire and interviews with students who were the object of research. The conclusion that can be drawn is that the dominant activity carried out by students is sleeping, by 30%. Meanwhile, students who study during empty hours are only 9%. The results of this study need to be followed up as evaluation material so that learning in schools becomes more effective in the future.